(untitled) (Research, Society and Development, 2023)
Digitalis mariana (Plantaginaceae) is considered native to Western, Southwestern and Central western Europe. It is a species of medicinal interest, given mainly by its cardiotonic glycosides used in the treatment of heart failure. Modifications in the culture medium can be performed to improve the in vitro culture. It has been reported that plant growth and development are affected by silicon application. Thus, the objective was to evaluate the growth, total cardenolide content and photosynthetic pigments in D. mariana cultivated under different sources and doses of silicon in culture medium. Plant material was established in vitro. After this process, three sources of Silicon were tested: Potassium, Calcium and Sodium silicate at concentrations of 0, 0.5, 1.5, 4.5, 7.5, 10.5 mg L-1. After 40 days, analytical validation was performed and growth, photosynthetic pigments and total cardenolides were evaluated. The different sources and concentrations promoted shoot and root growth, increased the levels of chlorophyll a, chlorophyll b, carotenoids and cardenolides. The use of 0.5 mg L-1 of sodium silicate promoted higher leaf and total dry biomass. Calcium silicate and potassium silicate at a concentration of 4.5 mg L-1 promoted higher levels of cardenolides. The cultivation of D. mariana under sources of silicon at different concentrations is a promising technique for optimizing the production of seedlings and secondary metabolites.